Characterization of polycyclic aromatic hydrocarbons in atmospheric aerosols collected from selected locations in peninsular Malaysia - Bahry, Pourya Shahpoury (2007)
With rapid modernization and development of Malaysia during the recent years, atmospheric hydrocarbons have been increasing due to increase in industrialization, motorization, biomass burning and deforestation in this country. One of the most important classes of hydrocarbons is polycyclic aromatic hydrocarbon (PAHs) that has long been of interest in the field of environmental forensic. It is very important to characterize the Polycyclic Aromatic Hydrocarbons in the environment because of the known carcinogenic and mutagenic effect of theses compounds to human health especially on the endocrine system. Generally, anthropogenic PAHs are released from both pyrogenic and petrogenic sources. Particulate phase PAHs have significant contribution from the total concentration of PAHs in the atmosphere. This study specifically focuses on characteristics of this group of compounds in total suspended particulates at nine sampling stations in peninsular Malaysia. The objectives of this project are to determine the sources, distribution and concentrations of compound specific PAHs in selected locations. For this purpose, atmospheric aerosols are collected using high volume air samplers. The samples are further soxhlet extracted using high-grade dichloromethane then purified and fractionated by a two-step column chromatography. Subsequently, PAHs fraction with 3-5 benzene rings is analyzed by gas chromatography coupled with mass spectrometer (GC-MS). The results of this study revealed that concentration of PAHs ranged from 0.28 to 13.02 ng/m3 with the mean value of 2.73 ng/m3. The ratio of the sum of methylphenanthrenes to phenanthrene (MP/P) was under unity for 16 samples from the 18 samples analyzed. This result indicated that the atmospheric PAHs are from pyrogenic sources. Interestingly samples from Tanah Rata station MP/P ratio were found to be above unity that may come from petrogenic input of PAHs. Application of lower molecular weight (LMW) to higher molecular weight (HMW) PAHs proportion provided very useful supportive data to identify the origin of PAHs. The results indicated that distribution of compound specific PAHs during the sampling period are strongly controlled by dominance of higher molecular weight PAHs, which is consistent with results of MP/P ratio. The only exceptions consist of two samples from Alor Setar and Tanah Rata stations that LMW/HMW and MP/P ratios do not relate to each other, suggesting unique source of PAHs in the study area that contains both pyrogenic and petrogenic PAHs. Finally, it has concluded that the atmospheric environment of peninsular Malaysia during the period of sampling has influenced by pyrogenic sources of PAHs.